2017
DOI: 10.1002/pc.24374
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of undeinked, alkaline deinked, and neutral deinked old newspaper fibers reinforced recycled polypropylene composites

Abstract: The properties of old newspaper fibers (ONPF) reinforced recycled polypropylene (rPP) composites (ONPF/rPP) have been studied. The effect of alkaline and neutral deinking treatments of ONPF was investigated. The tensile and flexural strength of ONPF/rPP composites were significantly improved when compared to the neat rPP. Composites from neutral deinked fibers showed slightly better mechanical strength than that reinforced by alkaline deinked fibers. The effect of the ONPF deinking treatment on the water absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Biodegradable green composites have emerged as the most high-potential substitute for petroleum matrix plastic to reduce concerns regarding the scarcity of oil resources and environmental pollution. [1][2][3][4] As biomass biodegradable plastic, poly(lactic acid) (PLA) has drawn interest because of its excellent biocompatibility, outstanding transparency, and easy processability. [5] However, the application of PLA is limited by its disadvantages, including high brittleness, low degree of crystallization, and hydrophily.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable green composites have emerged as the most high-potential substitute for petroleum matrix plastic to reduce concerns regarding the scarcity of oil resources and environmental pollution. [1][2][3][4] As biomass biodegradable plastic, poly(lactic acid) (PLA) has drawn interest because of its excellent biocompatibility, outstanding transparency, and easy processability. [5] However, the application of PLA is limited by its disadvantages, including high brittleness, low degree of crystallization, and hydrophily.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant advantages of PP is its thermoplastic behavior, allowing for the possibility of using a recycled resin as the matrix to produce composites, thereby developing a more environmentally friendly material, with properties similar to those of virgin PP. Recycled PP (rPP) was applied in several works, with different fibers [ 124 , 125 , 126 ]. However, only one work was found on combining rPP with SCG, where the rPP was obtained from waste espresso coffee capsules and was reinforced with 20 and 30 wt.% of espresso SCG, with and without MAPP (10 wt.% of the reinforcement amount).…”
Section: Scg Polymer Compositesmentioning
confidence: 99%
“…Our research team has found that old newspaper can solve the flocculation problem with low-dose gaseous methyltrichlorosilane (MTCS) treatment [23]. Some scholars had also investigated the impact of deinking methods of waste newspapers on the properties of composite materials [24]. In addition, the interface between the fiber and the matrix is an important factor affecting the properties of the polymer composite [25,26].…”
Section: Introductionmentioning
confidence: 99%